Perception and Use of E-mail: A Case Study in Universiti Utara Malaysia - Packeer Mohamed, Shafinah Farvin; Ku-Mahamud, Ku Ruhana; Ramli, Razamin; Abdullah, Kamarudin (Universiti Teknikal Malaysia Melaka, 2017)
E-mail has grown out to become as one of the most successful and frequently used computer applications since it was invented. It can be used to communicate faster, easier, and at a lower cost with everyone all over the world. Besides providing flexibility and improving the quality of communication, researchers acknowledged that there are many problems faced by e-mail users, namely repeating emails, spam e-mails, huge size attachment files, and insufficient storage size. A case study was conducted to investigate on Universiti Utara Malaysia staff’s perception and use of e-mail in order to improve the e-mail service provided to them. This paper discusses the findings from the study, which involves 958 staff. There were five phases involved in this study, which are instrument design, sampling, pilot study, data collection for real survey, and analysis. Self-administered questionnaires were used to gather the data, while descriptive statistical analysis was used for data analysis. The findings of the study reveal that UUM staff appreciate the e-mail service. However, they faced problems such as limited storage size and overwhelming number of e-mails. They believed that the UUM e-mail system is being abused as observed from the repeating advertisements and news sent to them. The output of this study can be used as a guideline by the UUM management in revising its e-mail policy so as to improve the quality of its e-mail service